Efficacy of Crude Soya oil and Emulsifier in Ration on Production Performance of Broilers - Srinivasan, G.; Nathan, N. Arul; Thanaseelaan, V.; Nanthini, A. Ruba (Indian Journal of Animal Nutrition, 2020)
This study was conducted to assess the efficacy of emulsifier in broiler ration containing crude soya oil on the production performance of broilers.Â  A total of 90 day- old Vencobb 320 broiler chicks were randomly divided into 15 groups of six birds in each and five groups were allocated to each dieary treatment. Treatment groups were fed with basal diet contains crude soya oil as energy source (T1), basal diet supplemented with fat emulsifier at the rate of 250 g per metric tonne of feed (T2) and 80 kcal energy reduced from basal diet supplemented with emulsifier at the rate of 250 g per metric tonne of feed (T3). All the chicks were reared under deep litter system for 42 days. Body weight and feed intake were recorded weekly. Â Body weight (6th week) of T2 birds (2622 g) was comparable with T3 (2558 g) but was higher (P